Modelling of decentralised blockchain applications development - Besançon, L.; Ghodous, P.; Gelas, J.-P.; Silva, C. F. da (Proceedings of the 2020 International Conference on High Performance Computing & Simulation (HPCS 2020), 2021)
The development of Decentralised Blockchain Applications (DBA) is becoming more and more complex. We formalise the development of DBA based on Business Process Modelling and ontologies. This formalisation permits to represent a set of specific constraints that characterise a DBA. These constraints concern data management, the Blockchain storage cost, the number of transactions allowed in a given time and the execution of the application logic. Based on this formalism, we propose a generic and adaptive methodology for the development of DBAs. This methodology uses as input the constraints related to each DBA and as output recommends a set of appropriate services necessary for the development of each DBA. For example, our methodology can recommend a specific distributed storage service such as InterPlanetary File System (IPFS) for a DBA that needs to handle a large amount of data. We apply our methodology to a Blockchain Video Game application.